Exploring linguistic landscapes in selected South African universities: A case study of the University of Cape Town and the University of the Western Cape - Adekunle, Tope Oluwakemi; Mheta, Gift; Mathonsi, Maleshoane Rapeane (Stellenbosch Papers in Linguistics Plus, 2019)
This study explores issues of language policy and language practice in the linguistic landscapes (LLs) of two South African universities located in the Western Cape province, namely the University of Cape Town (UCT) and the University of the Western Cape (UWC). It analyses language forms or modes as they are utilised in disseminating information in the public spaces of the higher institutions of learning, in line with Kress’s (2012: 205) assertion that modes are interactive channels of communication. This article specifically examines the modes of communication used in the selected universities, the influence of cultural overtones on language use and choice, and the depiction of power relations in the LLs of these universities. An in-depth, qualitative study was conducted using the explorative case study design. Data was collected in the form of photographs, and analysed thematically using Critical Discourse Analysis and Multimodality. The findings of this study reveal some contrasts between the National Language Policy of the Constitution of the Republic of South Africa 1996–2018, and the language practice portrayed in the public spaces of the selected campuses. They unveil incongruence between the espoused policy and policy in action. We examined the mode of presentation of the observed languages with regard to the language population of the institutions, authorship, and signage approaches (bottom-up and top-down placements). These presentation modes were considered in terms of their implications for practice and the move towards achievable racial and linguistic integration in these culturally, historically, politically, and linguistically diverse institutions. The study recommends a consistent implementation of language practice that is in harmony with the institutional, and the nation’s, language policy in a bid to ensure inclusivity in South Africa’s higher institutions of learning.